Role of photo stimuli on tourists’ attitudes and brand recognition of out-door advertisement / Mas Azianna Abdul Razak and Faiz Izwan Anuar - Abdul Razak, Mas Azianna; Anuar, Faiz Izwan (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Despite extensive research on advertising and its consequences, there is still a lack of research investigating modern and creative advertising strategy in shaping destination image. To fill the research gap, this quantitative approach study assesses the impact of tourism photo stimuli attributes on tourists’ attitude and brand recognition of outdoor advertisement. The findings revealed that photographic subject was the most influential factor for brand recognition and the lightbox billboard was rated the most attractive in advertising medium. However, there was no significant relationship detected between attitudes towards outdoor advertisement and brand recognition. Future research is needed to look into to other platform or medium of advertising and how they can influence tourists’ attitude and brand recognition.